TINJAUAN KEBUTUHAN AKTUALISASI DIRI KARYAWAN OPERASIONAL DI HOTEL GRAND ROCKY BUKITTINGGI - Mauliddy, Yozi; Chair, Ira Meirina; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2015)
This research aimed to describe about self actualitation needs operational employees in Grand Rocky Hotel Bukittinggi which in term of three indicators : achievement needs, safety needs and status needs. The type of this research is descriptive with qualitative data. Data collection techniques by using observation, interview and documentation. Based on the reseach about (1) achievement needs to do something better than the competitor, obtaining or passing through a dificult target, to develop the best way to do something already met properly. (2) Security needs include having a job that bring a sense of security, have protection from illness and disability, avoid the task with the risk of failure or error already met properly. (3) Status needs include having a vehicle according to the need alreadyÂ met properly, but stay in the righ medha environment and ncluded in the elite club have not been met properly.Key Word: Self Actualitation Needs, Operational Employee, Hotel